FUNGAL POPULATION, AFLATOXIN AND FREE FATTY ACID CONTENTS OF PEANUTS PACKED IN DIFFERENT BAG TYPES - SONIA S P BULAONG (SEAMEO BIOTROP, 2002)
Shelled peanuts of Gajah var. with initial moisture content of 7% were stored at 11 kg/bag in four bag types namely: jute bag, polypropylene bag, jute bag doubled with thin polyethylene (PE), and jute bag doubled with thick PE. Storage was done for six months under warehouse conditions with monitoring of relative humidity and temperature. Samples taken at the beginning of storage and every month thereafter were analyzed for moisture content, fungal population, aflatoxin and free fatty acid contents. Statistical analyses showed that moisture content, fungal population, and free fatty acid contents were significantly higher in jute and polypropylene bags than in PE-dou,bled jute bags. No significant differences were obtained in aflatoxin contents among bag types but at the end of six months storage, toxin level in jute bag exceeded the 30 ppb limit. Polypropylene had second highest toxin level at 23 ppb. The PE-doubled bags had 17 and 19 ppb total aflatoxins for thin and thick films, respectively. The results indicated that the immediate packaging of dried shelled peanuts at safe moisture level in plastic films with water vapor transmission rated of 1 g/m2/24 hr or lower is recommended. This packaging will delay critical increases in moisture content, fungal population, aflatoxin and free fatty acid contents of peanut kernels at ambient storage conditions. Keywords: Peanuts / bag types / fungal population / aflatoxin content / free fatty acid content.